ANTI-DIARRHEAL ACTIVITY AND TOXICITY OF LEARNG PID SAMUD RECIPE - Sireeratawong, Seewaboon; Khonsung, Parirat; Nanna, Urarat; Vannasiri, Supaporn; Lertprasertsuke, Nirush; Singhalak, Tipaya; Soonthornchareonnon, Noppamas; Jaijoy, Kanjana (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Learng Pid Samud (LPS) recipe is a traditional remedy in Thai folk medicine to ease the common diarrhea. The anti-diarrheal potential of LPS recipe was herein examined in vitro using a guinea-pig ileum model. The LPS exerted an inhibitory effect on acetylcholine-induced smooth muscle contraction in the guinea pig ileum. Significantly, not only did the LPS reduce the total amount of feces in the induced diarrhea rats, but also the intestinal transit in the charcoal meal test. A single oral administration with the recipe at 5,000 mg/kg did not cause acute toxicity and the daily oral administration (1,000, 2,000 and 4,000 mg/kg) for 90 days in rats did not produce any toxic signs and symptoms. In conclusion, the Learng Pid Samud recipe remedy is evidently safe and effective for the anti-diarrheal treatment which supports its therapeutic uses in the alternative medicine.